PENGARUH INTERAKSI TEMAN SEBAYA TERHADAP KEMAMPUAN BERSOSIALISASI SISWA DI LINGKUNGAN SEKOLAH - Norfa Anisa; Anis Tri Yuliana (STKIP Subang, 2026)
This study aims to determine the effect of peer interaction on students' socialization ability in the junior high school environment. The research used a quantitative associative design. The population and sample consisted of 20 nine-grade students of SMPI Darul Muttaqin selected through total sampling. Data were collected using a closed-ended Likert-scale questionnaire covering two variables: peer interaction and students' socialization ability. The data were analyzed using descriptive statistics, normality testing, simple linear regression, t-test, F-test, and coefficient of determination with the SPSS Statistics format. The results showed that peer interaction had a positive and significant effect on students' socialization ability, with t = 2.810, Sig. = 0.012, F = 7.898, and R Square = 0.305. These findings indicate that peer interaction explains 30.5% of the variance in students' socialization ability, while 69.5% is influenced by other factors outside the model. Thus, positive peer interaction needs to be strengthened through collaborative learning, group guidance, and school culture that supports communication, cooperation, empathy, and social acceptance among students.